Green Retailing: Environmental Strategies of Organized Retailers and Competitive Advantage (Global Business Management Review (GBMR), 2014)
Green Movement is becoming the buzzword of today’s business world. Across the world businesses are developing green strategies and thereby are working towards developing a low carbon landscape. Retailing is as old as business, trade and commerce and currently has revolutionized into new forms and formats. As the retail sector is quite energy intensive, retailers are left with no choice but to consider and adopt eco-friendly practices. The retailers serve as strategic touch point between producers and consumers and own the responsibility of offering green products and the greening of consumption. Green Retailing (GR) refers to the management approach that pursues environmental protection to improve the retail value chain through eliminating waste, increasing efficiency and reducing costs. Therefore, it is very important for the retailers to understand the perception and attitude of customers regarding the green image of the retailers. It aims to understand the factors that influence green buying behavior of customers under the green retail settings and how these green cues of store environment can influence consumer behavior as are their non-green counterparts in Indian context.